Acute myocardial infarction at a district hospital in KwaZulu-Natal – Management and outcomes - Zakariya Badat; Selvandran Rangiah (South African Family Practice)
Background: Acute myocardial infarction (AMI) following ischaemic heart disease (IHD) is associated with increased morbidity and mortality. The condition remains a management challenge in resource-constrained environments. This study analysed the management and outcomes of patients presenting with AMI at a district hospital in KwaZulu-Natal.